Pengaruh Terpaan Iklan Media Online Produk Wardah Terhadap Prilaku Mahasiswi Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Islam Makassar - Yunita Prastia Dewi; Andriansyah Andriansyah (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2021)
This study aims to determine how, the effect of exposure to online media advertisements for Wardah products on thebehavior of students at the Faculty of Social and Political Sciences, Makassar Islamic University. The type of researchused is quantitative research with data collection techniques through surveys and google form questionnaires with dataanalysis using Simple Linear Regression Analysis with the help of SPSS version 20. The results show that the influence ofexposure to online media advertisements for Wardah products on the behavior of students of the Faculty of Social andPolitical Sciences Makassar Islamic University so that H0 is rejected because there is no significant effect and Ha isaccepted because it has a strong and significant positive influence on buying interest in Wardah products, the effectgiven is 79.8% with a sig level. 0.000<0.005. While the remaining 20.2% is influenced by other factors.